PENGEMBANGAN BUKU PEDOMAN MICRO TEACHING UNTUK CALON GURU MATEMATIKA - Asmarani, Dewi; Zahroh, Umi (ALGORITMA: Journal of Mathematics Education, 2024)
AbstractThe Micro Teaching handbook provides a structured framework and outlines the steps for planning and implementing a Micro Teaching session. This study aimed to develop a valid Micro Teaching guidebook to improve the teaching skills of prospective mathematics teachers. The type of research used is R&D using the 4D model with the stages of define, design, develop, and disseminate. This research has not yet reached the disseminate stage. The subjects of this study consisted of 2 mathematics education lecturers as expert validators and 30 prospective mathematics teacher students as test subjects. The instruments used were questionnaires and Micro Teaching practice assessment sheets. The results showed that the Micro Teaching guidebook was declared valid. The results of the assessment of Micro Teaching practice showed an increase in the teaching skills of prospective mathematics teachers. The Micro Teaching guidebook can be used as a guide for prospective Mathematics teacher students in carrying out learning practices. AbstrakBuku pedoman Micro Teaching memberikan kerangka kerja yang terstruktur serta menguraikan langkah-langkah perencanaan dan pelaksanaan pada sesi Micro Teaching. Tujuan penelitian ini adalah mengembangkan buku pedoman Micro Teaching yang valid untuk meningkatkan keterampilan mengajar mahasiswa calon guru matematika. Jenis penelitian yang digunakan adalah R&D menggunakan model 4D dengan tahapan define, design, develop, dan disseminate. Penelitian ini belum sampai pada tahap disseminate. Subjek penelitian ini terdiri dari 2 orang dosen pendidikan matematika sebagai validator ahli dan 30 mahasiswa calon guru Matematika sebagai subjek uji coba. Instrumen yang digunakan berupa angket dan lembar penilaian praktik Micro Teaching. Hasil penelitian yang menunjukkan bahwa buku pedoman Micro Teaching dinyatakan valid. Hasil penilaian praktik Micro Teaching menujukkan peningkatan keterampilan mengajar para calon guru matematika. Buku pedoman Micro Teaching dapat digunakan sebagai panduan mahasiswa calon guru Matematika dalam melaksanakan praktik pembelajaran.